If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 72 + 4 + -14x = 36 Combine like terms: 72 + 4 = 76 76 + -14x = 36 Solving 76 + -14x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-76' to each side of the equation. 76 + -76 + -14x = 36 + -76 Combine like terms: 76 + -76 = 0 0 + -14x = 36 + -76 -14x = 36 + -76 Combine like terms: 36 + -76 = -40 -14x = -40 Divide each side by '-14'. x = 2.857142857 Simplifying x = 2.857142857
| (x+20)+(3x)=180 | | 12y^3-14y^2+4y=0 | | 5x+60=10x+10answer | | x^2+3x-130= | | 10x-106=4x-10 | | 3x-5y+19=1 | | X-10=-27 | | 5x+5=-103-7x | | -18=x-6 | | 8f+5=20 | | X-14=-26 | | 3(2y+4)*14=1 | | X-10=-13 | | 3x+4-5=4x+5 | | -25=x-3 | | X^3+3x^2+-4x=0 | | 3x+11=9x+22 | | X-16=-9 | | X-15=-11 | | X-14=-4 | | 17=x-3 | | 13-10x=39-17x | | -3-5x=-12 | | x+(x+1)=-9 | | 6(3+2x)-4=86 | | 64-2x=2x+20 | | 68+51y=17x | | 106-6x=12x+20 | | 3x+4=6x-(2) | | m^2+6m-72=0 | | 65-4x=5x+23 | | 4x-27x-7=0 |